A Recent Literature Review on Corporate Political Connections - Trinugroho, Irwan (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
It has always been an interesting issue deliberating the connectedness between corporation and political power. There have been a substantial number of papers in the academic literature empirically studying what so call “corporate political connections” over the last 17 years. Using 81 papers published in 2010-2017 in finance, economics, accounting, management and other journals, in this present paper, I provide a recent literature review on firm political connections particularly with respect to the empirical studies discussing the impact of being politically connected firms. A number of issues related to the effect of political connections on corporate strategy, behaviors and outcomes have been addressed. Few other papers provide different perspective by looking at the antecedents of corporate political connections and the contingency role of such connections. Little is found on the development of new measures of corporate political connections. Finally, it could be suggested that the interaction between political connections and the technological-based business innovation would be an interesting issue to study.